Mechanisms of retention on porous graphitic carbon: Chromatographic and computational chemistry studies - Simpson, David A (2001)
Porous graphitic carbon has been developed as a high-performance liquid chromatography stationary phase over the past 30 years. The evolution of PGC as a stationary phase was motivated by the desire to find a substitute for reversed-phase silica gel based materials in areas where these materials are inadequate (e.g. extremes of pH). However, PGC possesses a number of chromatographic properties which are thus far largely unexplained and differ from traditional silica-based reversed-phase supports. The retention mechanisms of mono-substituted benzenes and biphenyls on porous graphitic carbon stationary phase were investigated using chromatographic and computational methods.